2019
DOI: 10.1007/s00125-019-4831-3
|View full text |Cite
|
Sign up to set email alerts
|

NAD+ metabolism as a target for metabolic health: have we found the silver bullet?

Abstract: NAD + has gone in and out of fashion within the scientific community a number of times since its discovery in the early 1900s. Over the last decade, NAD + has emerged as a potential target for combatting metabolic disturbances and the mitochondrial dysfunction that is mediated through sirtuin (SIRT) enzymes. The beneficial metabolic effects of the NAD + /SIRT axis have triggered an increased interest in NAD + as an enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 82 publications
0
45
0
Order By: Relevance
“…Because of its essential role and ubiquitous presence, alterations of NAD + concentrations are associated with a large number of pathological conditions, including metabolic diseases like obesity, diabetes and insulin resistance, inflammation and immune responses(16,46,64). A decrease in NAD + levels is also a hallmark of aging and aging-associated pathologies, such as neurodegeneration and motor function decline.…”
mentioning
confidence: 99%
“…Because of its essential role and ubiquitous presence, alterations of NAD + concentrations are associated with a large number of pathological conditions, including metabolic diseases like obesity, diabetes and insulin resistance, inflammation and immune responses(16,46,64). A decrease in NAD + levels is also a hallmark of aging and aging-associated pathologies, such as neurodegeneration and motor function decline.…”
mentioning
confidence: 99%
“…Generation of precursors (glyceraldehyde 3-phosphate, ribose-5-phosphate and erythrose 4-phosphate) for nucleotide biosynthesis is a main function of PPP. In situations of intracellular fuel overload, shunting glycolytic intermediates into the PPP yields a relative energy loss in combination with an improved antioxidant and restorative capacity, via elevated cellular NADPH levels 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The potential therapeutic utility of NAD + supplementation was demonstrated as early as 1937 when it was demonstrated that it could cure the black tongue in the canine and successfully treat pellagra in the human [26][27][28]. Accordingly, more recent studies have shown that supplementation with NAD + precursors improves NAD + levels in aged tissues and thereby protects against aging and the development and progression of aging-related diseases [14,[29][30][31][32][33]. Indeed, boosting NAD + metabolism has been shown to extend the lifespan of various organisms, such as yeast, worms, flies, and rodents [11].…”
Section: Approaches To Increase Nad + Levels In Humansmentioning
confidence: 99%